A look into the Medical and Veterinary Entomology crystal ball. Issue 1 (August 2014) - DANTAS‐TORRES, F.; CAMERON, M. M.; COLWELL, D. D.; OTRANTO, D.
Abstract Medical and Veterinary Entomology (MVE) represents a leading periodical in its field and covers many aspects of the biology and control of insects, ticks, mites and other arthropods of medical and veterinary importance. Since the first issue of the journal, researchers working in both developed and developing countries have published in MVE, with direct impact on current knowledge in the field. An increasing number of articles dealing with the epidemiology and transmission of vector‐borne pathogens have been published in MVE, reflecting rapid changes in vector distribution, pathogen transmission and host–arthropod interactions. This article represents a gaze into the crystal ball in which we identify areas of increasing interest, discuss the main changes that have occurred in the epidemiology of parasitic arthropods since the first issue of MVE, and predict the principal scientific topics that might arise in the next 25 years for scientists working in medical and veterinary entomology.